Delayed minocycline but not delayed mild hypothermia protects against embolic stroke - Wang, Chen Xu (BioMed Central, 2002)
BACKGROUND: Inflammatory reactions occurring in the brain after ischemia may contribute to secondary damage. In the present study, effects of minocycline, an anti-inflammatory agent, alone or in combination with mild hypothermia on focal embolic cerebral ischemia have been examined. METHODS: Focal ischemic injury was induced by embolizing a preformed clot into the middle cerebral artery (MCA). Infarction volume was measured at 48 h after the injury. Mortality was also recorded. RESULTS: Delayed administration of minocycline alone or delayed minocycline plus delayed mild hypothermia reduced the infarction volume significantly. However, delayed mild hypothermia alone was not protective and delayed mild hypothermia in combination with minocycline did not show any additive effect. CONCLUSIONS: These results suggest that minocycline is beneficial in focal ischemic brain injury, and the lack of the enhanced neuroprotection may be due to the brief exposure to hypothermia.